Transfusion Transmission of Syphilis and HIV from Earlobe Piercing in Tattoo Clinic – A Case Study from the Coal Capital of India - Rishabh Kumar Rana; Ravi Ranjan Jha (NMO Journal)
The practices of body piercing and tattoos have gained popularity, but, they also pose a risk of transmitting diseases. This article details a case of a young male individual who acquired HIV subsequent to undergoing earlobe piercing at a nearby tattoo parlour. A 28-year-old male, who was in good condition overall, received a diagnosis of HIV following testing positive for treponema pallidum hemagglutination assay (TPHA) after frontal palmar rashes. The diagnosis of syphilis and HIV was incongruous with his stated behaviour, and the stated reasons were not acknowledged by the counsellors. The patient was notified about our research emphasis in the Department of Community Medicine and requested our aid in identifying the underlying reason for his HIV and TPHA positive. The patient and his parents had a thorough history assessment, which eliminated all recognised potential modes of HIV transmission. After ruling out all other possible means of transmission, it was determined that the patient’s HIV and TPHA positivity may be attributed to the use of a tattoo gun for earlobe piercing to insert diamond studs at a local tattoo parlour. The widespread establishment of tattoo parlours throughout the nation presents a potential hazard to adolescents, who may acquire HIV without participating in activities associated with the high risk of transmission. Tattoo parlours must provide education to their clients, adhere to strict hygienic and sterile protocols and undergo government inspections to verify compliance with hygiene and sterilisation regulations.